Discerning a Christian realism for today, with special reference to the attitudes of humility in Niebuhr's incidental writing, 1941-1952 - Lambert, Dennis Edson (The University of Edinburgh, 2005)
Humility is a defining attitude of Reinhold Niebuhr's Christian realism. His formal writing asserts humility as a divine grace that transforms the Christian's personal life and as a political virtue essential to meeting Christian social responsibilities. If the formal work develops the theological framework of humility his prolific incidental work illumines its operation within the exigencies of political life. Over his lifetime Niebuhr penned thousands of essays, articles and editorials on the issues of the day. For many American Christians and public intellectuals this body of his work provided insights of faith through which they read the signs of the times.

This dissertation examines the incidental writing from 1941-1952 to discern the relevance of humility in guiding American power during the 20th Century's most tumultuous era. From the incidental writing of this period four case studies are drawn in which we examine the operation of humility and its attitudes upon Niebuhr's insights into American power and international responsibility. In the first study humility is examined for its insights into Christian responsibility and the conduct of war. In the second we examine insights of humility that informed Niebuhr's understanding of the relationship between US power and the United Nations. The third case study examines the operation of humility in his account of the development and implementation of the Marshall Plan. And in the fourth the lens of humility is applied to the relationship between democratic self-criticism and the just use of power. The purpose of the case studies is not to claim that humility provides Christian realism a theological formula or policy blueprint for political action. Rather the cases demonstrate the operation of humility and its attitudes in Niebuhr's understanding of the facts, circumstances and foreseeable consequences necessary to discern a just use of American power in particular contexts

The discernments of humility reflected in the case studies are then applied to issues of contemporary America power. Here humility and its attitudes provide a lens through which we examine elements of the 2002 National Security Strategy, a document that embodies the Bush Administration's vision for the international role of American power today. Elements examined include the document's assertion of a distinctly American internationalism and its embrace of a preventative war doctrine. The conflict in Iraq provides the immediate context in which the lens of humility is applied to the National Security Strategy.

The dissertation concludes that Niebuhr's insights regarding the operation of Christian humility upon Christian responsibility inform a relevant Christian realism and enable it to speak truths of faith to American power today.